2022
DOI: 10.3390/chemengineering6050072
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitive Effect of Sebacate-Modified LDH on Concrete Steel Reinforcement Corrosion

Abstract: In recent decades, layered double hydroxides (LDH) have been proposed as innovative corrosion inhibitors for reinforced concrete. Their protective action is based on the ability to intercalate specific anions in the interlayer and on their ability to exchange the intercalated anion. In the present study, an organically charged LDH, with sebacate anions in the interlayer (LDH-S), is proposed as a water-repellent additive for mortar. The waterproofing efficiency of LDH-S and the associated corrosion inhibition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In this context, a dicarboxylate compound such as disodium sebacate (SB, C 10 H 16 Na 2 O 4 ), shown in Figure 1, is a suitable candidate to consider. Amidst the pursuit of environmentally benign inhibitors, in recent studies, SB has emerged particularly due to its potential for intercalation in the burgeoning field of a novel type of ceramic-based drug delivery system, namely layered double hydroxides, offering promise as an efficient smart pigment [5,13,25,26]. Thanks to the ion exchange properties inherent in such a lamellar ceramic structure, molecules such as corrosion inhibitors, once intercalated during synthesis or in a subsequent treatment phase, can be accommodated within the structure and gradually released in the presence of other ions, typically chlorides [27].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a dicarboxylate compound such as disodium sebacate (SB, C 10 H 16 Na 2 O 4 ), shown in Figure 1, is a suitable candidate to consider. Amidst the pursuit of environmentally benign inhibitors, in recent studies, SB has emerged particularly due to its potential for intercalation in the burgeoning field of a novel type of ceramic-based drug delivery system, namely layered double hydroxides, offering promise as an efficient smart pigment [5,13,25,26]. Thanks to the ion exchange properties inherent in such a lamellar ceramic structure, molecules such as corrosion inhibitors, once intercalated during synthesis or in a subsequent treatment phase, can be accommodated within the structure and gradually released in the presence of other ions, typically chlorides [27].…”
Section: Introductionmentioning
confidence: 99%
“…They found that LDHs have a positive impact on improving the carbonation resistance of cement paste. David Caballero et al [19] used an organically charged LDH with sebacate anions in the interlayer (LDH-S) as a water-repellent binder for mortar. They evaluate the waterproo ng e ciency and the corrosion inhibition ability of LDH-S in reinforced mortar samples.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue has received eighteen contributions, six review papers [1][2][3][4][5][6], and twelve research papers [7][8][9][10][11][12][13][14][15][16][17][18]. Most of the papers originated from groups who have previously worked with Prof. Rives, but five of the contributions came from authors who had not previously worked with him [6,7,13,17,18]. The materials most studied by Prof. Rives throughout his career were LDHs.…”
mentioning
confidence: 99%
“…The materials most studied by Prof. Rives throughout his career were LDHs. Therefore, it was not surprising that these materials were the basis of eight of the papers published in this Special Issue [2][3][4]10,11,[15][16][17]. Other materials included Ni-based catalysts [1], g-C 3 N 4 [5], mesoporous silica [6], MOFs [7], carbons [8,9], AlPO 4 [12], acid-modified clays [13], and porous aluminosilicates [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation